Electroanalysis of Imidacloprid Insecticide in River Waters Using Functionalized Multi-Walled Carbon Nanotubes Modified Glassy Carbon Electrode - Paiva, Wyslley Douglas A. (2019)
In this work, a functionalized multi-walled carbon nanotubes modified glassy carbon electrode (GCE/MWCNT-f) was optimized for the direct determination of imidacloprid (IMC) insecticide in river water. The functionalized material was characterized by infrared spectroscopy with Fourier transform (FTIR) and the modified electrode by scanning electron microscopy (SEM) and cyclic voltammetry (CV). Results revealed that the GCE/MWCNT-f effectively increased the response toward IMC reduction by enhancing the reduction peak current and decreasing the peak potential in comparison with the bare electrode. After optimizing the electroanalytical conditions, the GCE/MWCNT-f showed a linear voltammetric response at concentration ranging from 2.40 × 10−7 to 3.50 × 10−6 mol L−1, with detection and quantification limits of 4.15 × 10−7 mol L−1 and 1.38 × 10−6 mol L−1, respectively. The recovery rate of IMC in spiked river water samples varied from 90–95%. Thus, this sensor can be a promising tool for the analysis and monitoring of IMC in complex environmental matrices.